The role of glyceryl trinitrate, a nitric oxide donor, in acute stroke - Appleton, Jason Philip (2019)
Nitric oxide donors (e.g. glyceryl trinitrate (GTN)) are candidate treatments for acute stroke with haemodynamic, reperfusion, and neuroprotective properties. In order to establish the safety and efficacy of NO donors in acute stroke a Cochrane systematic review and meta-analysis was performed. Transdermal GTN was assessed in 5 trials (n=4197) in acute stroke. Overall, GTN was safe and lowered blood pressure but did not influence clinical outcome. However, early treatment with GTN within 6 hours (n=312) improved clinical outcomes across a variety of domains (death and dependency, death, disability, cognition, mood, and quality of life).